REFORMULASI INDEKS PENGUNGKAPAN ENTITAS SYARIAH DAN KEUNIKAN BERAGAM KEBIJAKAN NILAI SYARIAH DI BEBERAPA NEGARA - Septyan, Krisno (Jurnal Equity, 2016)
This research’s aim is to giving the altervative disclosure index for shariah company.Researcher’s used shariah enterprise theory to make a new disclosure index, the first step is combine among disclsoure index are AAOIFI Index, Islamicity disclsore index and Islamic Social Reporting, then eliminate a few point form those index based on shariah etics, academic’s perspective and regulation in some countries. In other side, researcher’s used content analysis method in six countries are Indonesia, Malaysia, Bahrain, Qatar, Iran and UK. Result is a make new disclosure index that showing the God is a highest stakeholder in company, care about all stakeholder such as employee, nature, duafa etc. While, content analysis’ result shows new found things related unique policy in each company in some countries.